NPR's podcast start up guide : create, launch, and grow a podcast on any budget - Weldon, Glen (Ten Speed Press, 2021)
From NPR comes the definitive guide to podcasting, featuring step-by-step advice on how to find a unique topic, tell the best stories, and engage the most listeners, as well as the secrets that will take a podcast to the next level.